2022
DOI: 10.21608/ejaj.2022.267637
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Parasitic Nematodes Associated with Certain Fruit Trees and Vegetable Crops in the North Eastern Egypt

Abstract: This survey was conducted in four locations of Ismailia governorate in the north eastern part of Egypt during the 2020-2022 seasons to investigate occurrence, population density and distribution of plant-parasitic nematodes associated with various crops. A total of 440 soil samples, were collected from infested fruit trees viz. grape (Vitis vinifera L.), guava (Psidium guajava L.), olive (Olea europaea L) and pomegranate (Punica granatum L.) and vegetable crops viz. green bean (Phaseolus vulgaris L.), pea (Pis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Tomato is the easy host for M. incognita which damage their roots, there are 720 juveniles/250 g of tomato rhizosphere (Adam et al, 2013). The density of M. incognita in Ismailia governorate was 720 individuals/ 250 g similar study in Egypt showed that for tomato and density of Tylenchorhynchus was 160 nematodes/ 250 g for tomato (Abdel-Baset et al, 2022).…”
Section: Discussionsupporting
confidence: 55%
“…Tomato is the easy host for M. incognita which damage their roots, there are 720 juveniles/250 g of tomato rhizosphere (Adam et al, 2013). The density of M. incognita in Ismailia governorate was 720 individuals/ 250 g similar study in Egypt showed that for tomato and density of Tylenchorhynchus was 160 nematodes/ 250 g for tomato (Abdel-Baset et al, 2022).…”
Section: Discussionsupporting
confidence: 55%
“…They can be either free-living or parasitic, feeding on plants, fungi, and animals (Decraemer & Hunt 2013). The species, which have adapted a plant-parasitic lifestyle, pose a significant threat to crop production worldwide (Sikora & Fernàndez 2005) and to solanaceous cultivated in soils of the Nile Valley and reclaimed sandy soils in the desert of Egypt (Mokbel et al, 2006;Abd-Elgawad et al, 2012;Abd-Elgawad, 2013 andMontasser et al, 2019). The root-knot nematodes consist of sedentary polyphagic root endoparasites (Sharon et al 2007) and their species are the most destructive plant-parasitic nematodes causing large economic losses in crop production (Sasser 1980).…”
Section: Introductionmentioning
confidence: 99%